Speculation, Sentiment, and Interest Rates - Buraschi, Andrea; Whelan, Paul (Management Science, 2022)
We compare the implications of speculation versus hedging channels for bond markets in heterogeneous agents’ economies. Treasuries command a significant risk premium when optimistic agents speculate by leveraging their positions using bonds. Disagreement drives a wedge between marginal agent versus econometrician beliefs (sentiment). When speculative demands dominate, the interaction between belief heterogeneity and sentiment helps rationalize several puzzling characteristics of Treasury markets. Empirically, we test model predictions and find that larger disagreement (i) lowers the risk-free rate, (ii) raises the slope of the yield curve, and (iii) with positive sentiment increases bond risk premia and makes its dynamics countercyclical. This paper was accepted by Karl Diether, finance.